Annexins as potential targets in ocular diseases - André da Silva, Rafael [UNESP]; Moraes de Paiva Roda, Vinicius; Philipe de Souza Ferreira, Luiz; Oliani, Sonia M. [UNESP]; Paula Girol, Ana [UNESP]; Gil, Cristiane D. [UNESP] (Elsevier, 2022)
Annexins (AnxAs) are Ca2+/phospholipid-binding proteins extensively studied and generally involved in several diseases. Although evidence exists regarding the distribuition of AnxAs in the visual system, their exact roles and the exact cell types of the eye where these proteins are expressed are not well-understood. AnxAs have pro-resolving roles in infectious, autoimmune, degenerative, fibrotic and angiogenic conditions, making them an important target in ocular tissue homeostasis. This review summarizes the current knowledge on the distribution and function of AnxA1–8 isoforms under normal and pathological conditions in the visual system, as well as perspectives for ophthalmologic treatments, including the potential use of the AnxA1 recombinant and/or its mimetic peptide Ac2–26.
Keywords: Angiogenesis; Annexins; Eye; Inflammation; Retina; Therapeutic target